Structural polymorphism research of alverine citrate - Magdalena Janczura; Natalia Rosiak; Marta Gromek; Judyta Cielecka-Piontek (Polskie Towarzystwo Farmaceutyczne, 2024)
The study compares the active substance alverine citrate from three commercial sources in order to demonstrate polymorphic forms using the XRPD, SEM, and ATR-FTIR techniques. Based on the solubility tests of alverine citrate, a hard capsule was prepared with the highest possible dose of the active substance. The release profiles of alverine citrate and its stability were also investigated. XRPD and ATR-FTIR analysis shows that all alverine citrate samples (despite differences in the synthesis process) are in the same polymorphic Form I. Scanning electron micrographs of alverine citrate from each manufacturer show differences in morphology (texture). The solubility studies confirmed the complete solubility of the highest dose of alverine citrate in media with a pH of 1.2-6.8. The release studies show that the release of the active substance, regardless of the manufacturer type, meets the immediate release requirement. Accelerated stability studies confirm the stability of the alverine citrate from selected manufacturers. As a result, the manufacturer of the final medicinal product may allow their inter-changeability during production without compromising the safety or efficacy of the medicinal product.